2016
DOI: 10.18176/jiaci.0039
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Efficacy of Antihistamines in Chronic Spontaneous Urticaria Based on Initial Suppression of the Histamine- Induced Wheal

Abstract: Background: Antihistamines are the first line of treatment for chronic spontaneous urticaria. However, there is no effective method to predict whether an antihistamine will have a beneficial clinical effect or not. Objective: To assess whether the change in histamine-induced wheal and flare measurements 24 hours after administration of antihistamine can predict the efficacy of treatment. Methods: We performed a multicenter, triple-blind, randomized study. Patients received a daily oral dose of cetirizine, fexo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
(33 reference statements)
0
21
0
Order By: Relevance
“…A recent review of 73 studies with 9759 participants, including adolescents over 12 years of age, although none of them included specific paediatric data, concluded that anti-H1 anti-histamine drugs are beneficial in less than 50% of cases [162]. More recently, a blind randomized controlled trial, performed on mixed adult and adolescent populations, confirmed the efficacy of cetirizine (10 mg), fexofenadine (180 mg), bilastine (20 mg), desloratadine (5 mg), ebastine (20 mg) [163]. In a non-controlled prospective study in subjects with AU or CU aged 11 to 92 years, levocetirizine 5 mg daily for 2–6 weeks greatly improved or resolved symptoms in 60–80% of patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of 73 studies with 9759 participants, including adolescents over 12 years of age, although none of them included specific paediatric data, concluded that anti-H1 anti-histamine drugs are beneficial in less than 50% of cases [162]. More recently, a blind randomized controlled trial, performed on mixed adult and adolescent populations, confirmed the efficacy of cetirizine (10 mg), fexofenadine (180 mg), bilastine (20 mg), desloratadine (5 mg), ebastine (20 mg) [163]. In a non-controlled prospective study in subjects with AU or CU aged 11 to 92 years, levocetirizine 5 mg daily for 2–6 weeks greatly improved or resolved symptoms in 60–80% of patients.…”
Section: Methodsmentioning
confidence: 99%
“…Second generation H1 antagonists are generally well tolerated [158, 162, 163, 165168], except for astemizole and terfenadine whose metabolism by P450 liver cytochrome can be blocked by the concomitant administration of ketoconazole or erythromycin, causing cardiotoxic effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a previously described cohort (URTICA project, ClinicalTrials.gov Identifier: NCT01940393 ) [ 6 ], we collected data from patients older than 12 years diagnosed with CSU, which was defined as the recurrence of hives for at least 6 weeks, in whom the diagnosis had been made by an allergist or a dermatologist. The severity of the disease and quality of life were evaluated with UAS (Urticaria Activity Score) and DLQI (Dermatology Life Quality Index), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The second‐generation non‐sedating H1 antihistamines are the first choice for the treatment of CSU . Non‐sedating H1 antihistamine drugs mizolastine, desloratadine and fexofenadine are widely used as H1‐receptor antagonist.…”
Section: Introductionmentioning
confidence: 99%